A Systematic Algorithm after Cardiac Arrest is Feasible and Effective - Kuznar, Wayne (MD Conference Express, 2014)
A systematic diagnostic and therapeutic algorithm, which includes urgent catheterization, following cardio-pulmonary resuscitation is feasible and is associated with improved patient outcome. This article presents results from a prospective study assessing a systematic approach to managing patients following resuscitation.